2017
DOI: 10.3390/rs9090919
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Land Surface Temperature Change under Urban Landscape Renewal: A Case Study in the Main City of Shenzhen, China

Abstract: Abstract:Unprecedented rapid urbanization in China during the past several decades has been accompanied by extensive urban landscape renewal, which has increased the urban thermal environmental risk. However, landscape change is a sufficient but not necessary condition for land surface temperature (LST) variation. Many studies have merely highlighted the correlation between landscape pattern and LST, while neglecting to comprehensively present the spatiotemporal diversification of LST change under urban landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…In addition, the inherent characteristic of the Globcover product to define as urban the artificial surfaces including all non-vegetative and human-constructed facilities that cover greater than 50% of a given landscape unit leads to heterogeneous urban pixels which in turn leads to large spatial variability especially during daytime. In [73][74][75] it is demonstrated that land cover composition and configuration greatly affects the magnitude of LST and that LST differs according to different landscape types, and the proportion of landscape types is the most significant factor affecting LST.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inherent characteristic of the Globcover product to define as urban the artificial surfaces including all non-vegetative and human-constructed facilities that cover greater than 50% of a given landscape unit leads to heterogeneous urban pixels which in turn leads to large spatial variability especially during daytime. In [73][74][75] it is demonstrated that land cover composition and configuration greatly affects the magnitude of LST and that LST differs according to different landscape types, and the proportion of landscape types is the most significant factor affecting LST.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown the close relationship between urbanization and the change in urban thermal environments, as evidenced by higher LST [15,[51][52][53]. But what is the actual impact of urban renewal on LST?…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The winter in Shenzhen is warm enough to sustain plant growth, so almost all local plants are evergreen [62]. As a result, the ET rate of the H. littoralis hedge was still high in the winter day.…”
Section: The Et Characteristics Of Urban Hedgesmentioning
confidence: 99%